Konflik Arab – Israel Di Palestina - Susmihara Susmihara (Jurnal Adabiyah: Humanities and Islamic Studies, 2011)
Palestina is a continously conflicted region. Thousand years before christus, Jews has already established the Judah King and Israel. These regions were occupied interchangably by some nations such as Assyiria, Babylonia, Misria, Persia, Macedonia, Romawi and Byzantium.  Arabian then took Palestina form caisar of Byzantium  (634 M) and in 1516 M., Palestina was under Turki Usmani kingdom. In  this time, Jews cameback to Paletine, and lived with arabian in harmony based on culture and religion. However, some leaders of Israel formed zionisme by means to establish Jews Nation. This movement finally became the main factor of conflict